2017
DOI: 10.1002/cplu.201700296
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Reaction Monitoring of an Organic Multistep Reaction by Electrospray Ionization‐Ion Mobility Spectrometry

Abstract: The capability of electrospray ionization (ESI)‐ion mobility (IM) spectrometry for reaction monitoring is assessed both as a stand‐alone real‐time technique and in combination with HPLC. A three‐step chemical reaction, consisting of a Williamson ether synthesis followed by a hydrogenation and an N‐alkylation step, is chosen for demonstration. Intermediates and products are determined with a drift time to mass‐per‐charge correlation. Addition of an HPLC column to the setup increases the separation power and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…42,43 These methods are often used in combination to provide the fullest possible reaction understanding, covering different levels of analyte specificity and limits of detection. 44 In this study, we investigated the development and application of computer vision as a camera-based method (an in-line complement to existing off-line analytical methods) for providing data-rich, real-time, and non-contact kinetic information on the widespread problem of Pd catalyst degradation processes. Our colorimetric kinetics method is explored as an operationally cheap and simple method (relative to the setup of more common spectroscopic reaction monitoring methods) of obtaining macroscopic kinetic information from the reaction bulk.…”
Section: Introduction Catalyst Degradationmentioning
confidence: 99%
“…42,43 These methods are often used in combination to provide the fullest possible reaction understanding, covering different levels of analyte specificity and limits of detection. 44 In this study, we investigated the development and application of computer vision as a camera-based method (an in-line complement to existing off-line analytical methods) for providing data-rich, real-time, and non-contact kinetic information on the widespread problem of Pd catalyst degradation processes. Our colorimetric kinetics method is explored as an operationally cheap and simple method (relative to the setup of more common spectroscopic reaction monitoring methods) of obtaining macroscopic kinetic information from the reaction bulk.…”
Section: Introduction Catalyst Degradationmentioning
confidence: 99%
“…In recent years, IMS has experienced a renaissance, especially through the combination with electrospray mass spectrometers and the commercial availability of corresponding instruments. While such IMS-MS systems are extremely powerful analytical tools, they have lost the advantages of stand-alone IMS systems such as their small size, instrumental simplicity, robustness, and comparatively low cost. Typical drift tube IMS, for example, has a tube length of only 5–20 cm and can nowadays already be 3D-printed. Although the main focus of IMS is still presented in the gas-phase analysis, it has been demonstrated that IMS is an attractive detector for monitoring liquid-phase chemical and biochemical reactions. Zühlke et al presented a qualitative and quantitative determination of all reaction components of an organic three-step synthesis . Very recently, IMS was also applied for monitoring photocatalyzed isomerization reactions performed on a continuous-flow microchip reactor …”
Section: Introductionmentioning
confidence: 99%
“…The combination of these properties makes IM spectrometry attractive for reaction monitoring. IM spectrometry in combination with ESI was previously used for reaction monitoring of a three-step synthesis [ 29 ]. The coupling of a microchip-based HPLC separation and IM spectrometry was also shown [ 30 ], demonstrating the potential of chip-HPLC/IM spectrometry as a miniaturized two-dimensional separation method for separating three isomeric antidepressants.…”
Section: Introductionmentioning
confidence: 99%